2006
DOI: 10.1001/archpsyc.63.12.1386
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Sensitization to Stimulants in Humans

Abstract: Sensitization to stimulants can be achieved in healthy men in the laboratory. This phenomenon is associated with increased dopamine release and persists for at least 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(120 citation statements)
references
References 87 publications
9
110
1
Order By: Relevance
“…For example, amphetamine sensitization in rats increases specific firing patterns of neurons in mesolimbic structures that code the incentive salience of a reward CS (Tindell et al 2005). In humans, repeated amphetamine treatment is reported to sensitize amphetaminestimulated dopamine 'release' in the ventral striatum, even a year after the last drug treatment (Boileau et al 2006), and a sensitization of dopamine release has also been reported in patients with DDS (Evans et al 2006). In conclusion, even if we are unsure at this point about exactly which of the many changes in the brain produced by drugs underlie the psychological change of incentive sensitization, we suggest that the evidence provided above indicating that repeated drug exposure alters the relevant behaviours, psychological processes and brain structures themselves in the predicted directions is prima facie evidence for the thesis.…”
Section: What Is Sensitization?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, amphetamine sensitization in rats increases specific firing patterns of neurons in mesolimbic structures that code the incentive salience of a reward CS (Tindell et al 2005). In humans, repeated amphetamine treatment is reported to sensitize amphetaminestimulated dopamine 'release' in the ventral striatum, even a year after the last drug treatment (Boileau et al 2006), and a sensitization of dopamine release has also been reported in patients with DDS (Evans et al 2006). In conclusion, even if we are unsure at this point about exactly which of the many changes in the brain produced by drugs underlie the psychological change of incentive sensitization, we suggest that the evidence provided above indicating that repeated drug exposure alters the relevant behaviours, psychological processes and brain structures themselves in the predicted directions is prima facie evidence for the thesis.…”
Section: What Is Sensitization?mentioning
confidence: 99%
“…Neural evidence of sensitization has also been described recently in humans, as mentioned above. Repeated intermittent administration of amphetamine causes sensitization of dopamine release in humans, even when a drug challenge is given a year later (Boileau et al 2006), and drug cues also elicit a vigorous dopamine response in the same reward-related brain structures (Boileau et al 2007; see also Childress et al 2008). Intriguingly, a similar sensitized dopamine response to L-DOPA occurs in Parkinson's patients with the so-called DDS (Evans et al 2006).…”
Section: Does Sensitization Occur In Humans?mentioning
confidence: 99%
“…This finding demonstrates that the initial exposure resulted in an "increased sensitivity to the reinforcing properties of the drug," because of which subjects were more motivated to consume the drug during subsequent trials as compared to controls. More recently, a study by Boileau et al reported that when treated with three doses of amphetamine within the span of five days, healthy adult men demonstrated an increased release of dopamine in response to the third dose relative to the first (Berger et al 1996;Boileau et al 2006). When participants were re-tested a year later, they continued to demonstrate dopaminergic sensitization in brain areas such as the ventral striatum, which is involved in the regulation of "wanting."…”
Section: Evidence For the Incentive Sensitization Theorymentioning
confidence: 99%
“…Persistence of psychotic experiences may be related to an underlying process of dopamine sensitization, associated with repeated exposure to environmental risk factors acting on a final common pathway (Boileau et al, 2006;Collip et al, 2008;van Winkel et al, 2008). Only the Persistent developmental trajectory was consistently associated with many factors that predict or are associated with transition to clinical psychosis.…”
Section: Persistence Of Psychotic Experiencesmentioning
confidence: 99%